(untitled) (Docentes 2.0 Journal, 2016)
It is pertinent to remember that not all of us learn the same, nor at the same promptness. In any classroom, where people begin to study a material all together and starting from the same level, we will encounter the passing of time with great differences in the knowledge of each member of the group and that despite the fact that apparently all They have received the same explanations and done the same activities and exercises. Each member of the group will learn differently, will have different doubts and will advance more in some areas than in others.